2018
DOI: 10.1021/acs.chemmater.8b01446
|View full text |Cite
|
Sign up to set email alerts
|

Transparent, Adhesive, and Conductive Hydrogel for Soft Bioelectronics Based on Light-Transmitting Polydopamine-Doped Polypyrrole Nanofibrils

Abstract: Conductive hydrogels are promising materials for soft electronic devices. To satisfy the diverse requirement of bioelectronic devices, especially those for human–machine interfaces, hydrogels are required to be transparent, conductive, highly stretchable, and skin-adhesive. However, fabrication of a conductive-polymer-incorporated hydrogel with high performance is a challenge because of the hydrophobic nature of conductive polymers making processing difficult. Here, we report a transparent, conductive, stretch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
273
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(276 citation statements)
references
References 67 publications
0
273
1
2
Order By: Relevance
“…Han et al demonstrated that programmable changes in the adhesion strength of hydrogel, which are synthesized by in situ formation of polydopamine (PDA)-doped polypyrrole nanofibrils, interwoven in an elastic and transparent polyacrylamide network, resulted in controllable values up to 30 kPa in maximum. [211] Moreover, Oh et al recently demonstrated a resistor-type temperature sensor exhibiting high thermal sensitivity of 2.6% °C −1 (25-40 °C), enabled by the integration of the use of functional hydrogel and the aforementioned hierarchical layout of the surface (Figure 8g). [212] They designed PDMS surfaces according to bioinspired octopus sucker-like microstructures that have a cavity (7.5 µm) and rim (4 µm).…”
Section: Adhesionmentioning
confidence: 99%
“…Han et al demonstrated that programmable changes in the adhesion strength of hydrogel, which are synthesized by in situ formation of polydopamine (PDA)-doped polypyrrole nanofibrils, interwoven in an elastic and transparent polyacrylamide network, resulted in controllable values up to 30 kPa in maximum. [211] Moreover, Oh et al recently demonstrated a resistor-type temperature sensor exhibiting high thermal sensitivity of 2.6% °C −1 (25-40 °C), enabled by the integration of the use of functional hydrogel and the aforementioned hierarchical layout of the surface (Figure 8g). [212] They designed PDMS surfaces according to bioinspired octopus sucker-like microstructures that have a cavity (7.5 µm) and rim (4 µm).…”
Section: Adhesionmentioning
confidence: 99%
“…Furthermore, electrophysiological sensors can record important information about health by visualizing human body electrical signals into diagrams, such as the electrocardiogram (ECG), electromyogram (EMG), and electroencephalogram (EEG) . Various flexible and conformable electrophysiological sensors have been developed for long‐term monitoring electrophysiological signals.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesive materials play a significant role in industrial and biomedical fields, which have been widely applied into various applications, including soft robots, [1] wound dressing, [2,3] wearable devices, [4][5][6] and 3D printing [7,8] in water or oil. Up to now, intense endeavor has been devoted to revolutionizing adhesion science and technology for developing more promising applications.…”
Section: Introductionmentioning
confidence: 99%